Reflections and Pattern Recognition in Problem Based Learning - Torgal, Vaishnavi; Hegade, Prakash; Shettar, Ashok (Journal of Engineering Education Transformations, 2025)
Problem based learning, being student-centered, has been widely used in education programs to enhance the learning process. Self-directed learning and critical thinking are major aspects of the pedagogy among several others. Reflections are generally used to capture the student’s understanding during problem-solving. While problems can be designed and solved with supporting learning styles and strategies, computational thinking can aid in the process. Pattern recognition being one of the components of the model can assist in writing reflections. This work proposes to combine pattern recognition into reflection element. The designed case study model was qualitatively and quantitatively analyzed on 37 student’s data. Descriptive and In vivo coding was used for round one, which was used to analyze the student reflections on the provided case study. Focus coding was used for round two to identify the evaluation parameters. The parameters were then used for the quantitative analysis. The work presents the themes and codes that were identified in the process. With pattern recognition in the reflections, students were able to relate to the principles studied in the past and arrive at better applicative thought process. Using pattern recognition promises to be an effective strategy to guide towards meaningful reflections.